COMPARISON OF SAMPLING METHODS AND DEVELOPMENT OF A SEQUENTIAL SAMPLING FOR CHRYSOMELIDS AND LEAF-KEEPERS IN BEANS - VELÁSQUEZ-M., JUAN GUILLERMO; CARDONA-MEJÍA, CÉSAR (Revista Colombiana de Entomología, 1982)
Direct observation, cloth, D-Vac and Sweepnet methods of capture were compared against an absolute method of sampling, in order to find out their efficiency in estimating populations of Diabrotica balteata LeConte, Cerotoma facialis Erickson (Coleoptera: Chrysomelidae) and the leafhopper Empoasca kraemeri Ross and Moore (Homoptera: Cicadellidae) on beans. The spatial distribution of these insects, in which economic damage levels have already been established, was studied with the best sampling methods. A sequential sampling model was also developed. Direct observation and D-Vac were efficient for all of the insects. The cloth method was efficient for D. balteata and chrysomelid complex. The sweep net was efficient for estimating E. kraemeri adults, and the only method available for estimating E. kraemeri nymphs was the direct observation. Though there were differences between crops, the !spatial distribution was generally contagious for chrysomelids and nymphs of the leafhoppers. For these species, the models which fit the best were the binomial negative and the Neyman type A. The regression calculation between aggregation means and population means, permitted to calculate the necessary decision lines for developing a sequential plan for leafhopper and chrysomelids on beans.